Strategi Penjualan Produk Sepeda Motor Yamaha Melalui Analisis Structure, Conduct and Performance (SCP) - Ardella Naffa Ramadhini; Hanifah Ulul Azmi; Aan; Kenti Wahyuningsih; Naerul Edwin Kiky Aprianto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This study discusses the importance of product sales in the context of effective marketing strategies in the era of globalization and intense market competition. Using a qualitative descriptive approach, this research analyzes the relationship between market structure, company behavior, and market performance through the Structure Conduct Performance (SCP) analytical framework. Literature studies and case analyses of companies, such as the research by Apriyanti and Ramadhani (2018) on palm oil marketing, indicate that oligopolistic market structures influence pricing and product strategies. This study also identifies factors affecting sales, including market conditions, seller capabilities, capital, and product innovation. The findings show that companies implementing aggressive and responsive marketing strategies to changing consumer preferences can achieve better market performance, as evidenced by PT Yamaha with its Nmax product, which has become one of the best-selling motorcycles in Indonesia. These findings emphasize the importance of understanding market structure and consumer behavior in formulating effective sales strategies to enhance competitiveness and company performance